''Psychologists'' Experiences Concerning Premature Dropouts/This Study is Conducted for the Fulfilment of the BSc in Applied Psychology - Loupou Eleni; Thalassinos Stavros (2019)
Declaration, Acknowledgements, Abstract, Introduction, Methodology, Analytical Methodology, Data Collection, Materials, Sample and Participant, Procedure, Data Analysis, Ethics, Reflexivity, Analysis, Discussion, Conclusion, References, Information Sheet, Brief Form, Consent Form, Debrief Form, Interview Schedule, Spidergraph, Table of Themes, Personal Development Plan, Coursework Checklist.